Trade union action in the prevention and fight against psychological harassment at the workplace: is it effective? - Ciampa Benhame Puglisi, Maria Lúcia (2019)
In recent years, workplace harassment cases have multiplied and ceased to be reserved from one or another society to become a common reality of our times. Although there has been an attempt to solve this problem from legislative policies, it is also important to consider the role of trade unions. In this article, the author examines from web  platforms the eff ect and presence of trade unions on specifications in the prevention and fi ght against psychological harassment on Brazil workplaces. To achieve this, comparative case law, union agreements and news from Brazil and other countries press agencies have been considered.